Effect of Pharmacist-Led Interventions on Medication Adherence among Vietnamese Patients with Asthma: A Randomized Controlled Trial - Tan Thanh Nguyen; Mai Thi Xuan Truong; Dung Ngoc Lam; Tuyen Thi Thanh Le; Mai Tuyet Vi; Thanh My Tran; Thu Pham Minh Vo; Suol Thanh Pham; Bao Lam Thai Tran; Thang Nguyen; Lam Van Nguyen (Advances in Respiratory Medicine, 2023)
Background: Medication adherence in asthmatic patients enhances the effectiveness of treatments, but some studies in low and middle-income countries still show some limitations. Our study aimed to determine if pharmacist-led interventions could increase medication adherence, improve treatment effectiveness, and relieve symptom severity in outpatients with asthma. Methods: We conducted a randomized, controlled trial on 247 asthmatic outpatients (aged ≥ 16) with a 1:1 ratio randomization at the hospitalization time and repeated after 1-month discharge. The primary outcome was to detect the difference in medication adherence between groups. Adherence was assessed by the general medication adherence scale (GMAS). Data collected by questionnaire was coded and entered into SPSS_20 for statistical analysis; Results: 247 patients (123 intervention, 124 control) were enrolled (61.1% male). After intervention, the adherence rate was higher among the intervention group than the control group (94.3% vs. 82.8%, p = 0.001). Patient behavior and knowledge were enhanced in the intervention group (p < 0.05). Asthma symptoms were relieved in the intervention group (p = 0.014). Pharmacist-led interventions on adherence rate were higher with OR: 3.550, 95% CI: 1.378–9.143, p = 0.009. Conclusions: pharmaceutical intervention could improve medication adherence, treatment efficacy, and the outcome should not be taken for granted; further research should be carried out in this regard.